2019
DOI: 10.2215/cjn.13091118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment of Metabolic Acidosis in CKD

Abstract: Background and objectives Metabolic acidosis is associated with progression of CKD and has significant adverse effects on muscle and bone. A systematic review and meta-analysis was conducted to evaluate the benefits and risks of metabolic acidosis treatment with oral alkali supplementation or a reduction of dietary acid intake in those with CKD. Design, setting, participants, & measurements MEDLINE, Embase, and Cochrane CENTRAL were searched for relevant trials in patients with stage 3-5 CKD and metabolic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 36 publications
(59 reference statements)
4
79
0
1
Order By: Relevance
“…Bicarbonate concentrations in the placebo group rose gradually over time, which again limited the contrast between the two groups; this may be due in part to the pragmatic nature of the trial design, where physicians were free to switch participants to bicarbonate therapy if this was felt to be clinically indicated. The effect seen in both recent systematic reviews [9,10] was greater than that observed in the current trial, with a mean 3 mmol/L higher serum bicarbonate in the treatment arm compared to control by the end of follow-up; restricting analyses to 1-year followup gave similar results. It is likely that the combination of a modest dose of bicarbonate (in comparison to some Fig.…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 49%
See 1 more Smart Citation
“…Bicarbonate concentrations in the placebo group rose gradually over time, which again limited the contrast between the two groups; this may be due in part to the pragmatic nature of the trial design, where physicians were free to switch participants to bicarbonate therapy if this was felt to be clinically indicated. The effect seen in both recent systematic reviews [9,10] was greater than that observed in the current trial, with a mean 3 mmol/L higher serum bicarbonate in the treatment arm compared to control by the end of follow-up; restricting analyses to 1-year followup gave similar results. It is likely that the combination of a modest dose of bicarbonate (in comparison to some Fig.…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 49%
“…Few trials have tested whether sodium bicarbonate is effective at preventing adverse outcomes from advanced CKD, and is safe in the context of increased sodium load, as opposed to merely increasing the concentration of circulating bicarbonate. Two recent systematic reviews and metaanalyses of small trials of moderate quality suggested a modest beneficial effect on estimated GFR and serum bicarbonate, an uncertain effect on progression to endstage kidney disease and contrasting effects on blood pressure (no effect in one review, and a small increase in the risk of hypertension in the other), and found no data on the effect of bicarbonate on physical function or quality of life [9,10]. The mean age of participants in included trials was young, ranging from 41 to 65 years.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, to raise serum bicarbonate by 3 -4 mEq/L in an 80 kg patient, 6 to 8 g/day of sodium bicarbonate are required, delivering 1.7 − 2.2 g/day of sodium in addition to normal dietary sodium intake (Abramowitz et al, 2013), thus exceeding the published guidelines for daily sodium intake in patients with CKD (Wright and Cavanaugh, 2010). This additional sodium has the potential to aggravate sodiumsensitive comorbidities such as hypertension, congestive heart failure and edema in patients with CKD (Bushinsky, 2019;Navaneethan et al, 2019). The additional sodium load from sodium-This article has not been copyedited and formatted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is increasing evidence that chronic MA can lead to progression of CKD [9][10][11][12][13][14]. In addition, alkalinizing therapies in CKD patients reduced the decline of GFR in several randomized controlled trials (RCTs) [15][16][17][18][19][20][21]. Consequently, the KDIGO guidelines suggest bicarbonate substitution in CKD patients if serum bicarbonate concentration is <22 mmol/L [1].…”
Section: Introductionmentioning
confidence: 99%